Increase in neurokinin-1 receptor-mediated colonic motor response in a rat model of irritable bowel syndrome - La, Jun-Ho (Baishideng Publishing Group Co., Limited, 2005)
AIM: Irritable bowel syndrome (IBS) is a functional bowel disorder. Its major symptom is bowel dysmotility, yet the mechanism of the symptom is poorly understood. Since the neurokinin-1 receptor (NK(1)R)-mediated signaling in the gut is important in the control of normal bowel motor function, we aimed to investigate whether the NK(1)R-mediated bowel motor function was altered in IBS, using a rat IBS model that was previously reported to show colonic dysmotility in response to restraint stress. METHODS: IBS symptoms were produced in male Sprague-Dawley rats by inducing colitis with acetic acid. Rats were left to recover from colitis for 6 d, and used for experiments 7 d post-induction of colitis. Motor activities of distal colon were recorded in vitro. RESULTS: The contractile sensitivity of isolated colon to a NK(1)R agonist [Sar(9),Met(O(2))(11)]-substance P (1-30 nmol/L) was higher in IBS rats than that in normal rats. After the enteric neurotransmission was blocked by tetrodotoxin (TTX, 1 μmol/L), the contractile sensitivity to the NK(1)R agonist was increased in normal colon but not in IBS rat colon. The NK(1)R agonist-induced contraction was not different between the two groups when the agonist was challenged to the TTX-treated colon or the isolated colonic myocytes. A nitric oxide synthase inhibitor Nω-nitro-L-arginine methyl ester (L-NAME, 100 μmol/L) augmented the NK(1)R agonist-induced contraction only in normal rat colon. CONCLUSION: These results suggest that the NK(1)R-meidated colonic motor response is increased in IBS rats, due to the decrease in the nitrergic inhibitory neural component.